1996
DOI: 10.1111/j.1346-8138.1996.tb04054.x
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Scleroderma with PUVA Therapy

Abstract: PUVA therapy was carried out on four patients with scleroderma; three of them had cutaneous manifestations of progressive systemic sclerosis and one other exhibited generalized morphea. PUVA therapy was given with daily doses of 0.25J/cm2 or 0.4J/cm2 for 3-8 weeks, resulting in total doses between 3.5J/cm2 and 9.6J/cm2. All four patients responded well to this treatment; improvements of hand closure, skin sclerosis index, and flexion of fingers or knee joints were obtained. Thus, PUVA appeared to be beneficial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 8 publications
1
25
0
2
Order By: Relevance
“…Discussion PUVA photochemotherapy has been used to treat patients with localized and systemic scleroderma with good results (1)(2)(3)(4). In the present report, we describe an additional case of localized scleroderma which re sponded dramatically to topical PUVA ther apy.…”
Section: Case Reportmentioning
confidence: 92%
“…Discussion PUVA photochemotherapy has been used to treat patients with localized and systemic scleroderma with good results (1)(2)(3)(4). In the present report, we describe an additional case of localized scleroderma which re sponded dramatically to topical PUVA ther apy.…”
Section: Case Reportmentioning
confidence: 92%
“…Score went from three to one. Disease free after 2-year follow-up with weekly maintenance therapyNoKanekura et al [95]Case report61/MProgressive systemic sclerosisPUVA0.25 J/cm 2 4 times a week. Total dose of 5 J/cm 2 .Unavailable5 weeks20Hand closure and skin sclerosis index improved from 4 to 1NoKanekura et al [95]Case report42/MProgressive systemic sclerosisPUVAPUVA 0.4 J/cm 2 6 times a week.…”
Section: Clinical Evidence Of Phototherapy’s Efficacymentioning
confidence: 99%
“…Total dose of 5 J/cm 2 .Unavailable5 weeks20Hand closure and skin sclerosis index improved from 4 to 1NoKanekura et al [95]Case report42/MProgressive systemic sclerosisPUVAPUVA 0.4 J/cm 2 6 times a week. Total dose of 7.2 J/cm 2 .Unavailable3 weeks18Hand closure and skin sclerosis index improved from 3 to 0NoKanekura et al [95]Case report32/FProgressive systemic sclerosisPUVAPUVA 0.25 J/cm 2 twice a week. Total dose of 3.5 J/cm 2 .Unavailable7 weeks14Skin sclerosis index improved from 3 to 1NoKanekura et al [95]Case report80/MLocalized sclerodermaPUVAInitial 3 times weekly UVA dose of 4 J/cm 2 , which was gradually increased, weekly, to a maximal single dose of 18 J/cm 2 Unavailable11 months127After 9 months, the skin plaques were softening.…”
Section: Clinical Evidence Of Phototherapy’s Efficacymentioning
confidence: 99%
“…Recent studies have demonstrated that topical and systemic PUVA therapy, i.e., ultraviolet A (UVA) irradiation following treatment with 8-methoxypsoralen , is effective against the sclerotic skin lesions in SSc [1][2][3]. However, the mechanisms underlying the improvement of the skin sclerosis in scleroderma with PUVA therapy remain unknown.…”
Section: Introductionmentioning
confidence: 99%